Studi Meta Analisis : Peningkatan Kemampuan Literasi Biodiversitas Berdasarkan Model Pembelajaran dan Tingkat Pendidikan - Siti Rabiatul Fajri; AAIA Rai Sudiatmika; I Ketut Suma; I Nyoman Suardana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This research aims to analyze the increase in biodiversity literacy skills based on learning methods and level of education. Apart from that, this research also analyzes indicators of biodiversity literacy. The research analyzed 8 reputable international journals with 6 learning methods, 4 levels of education, and 10 biodiversity literacy assessment indicators. The research was carried out with meta analysis in the form of effect size analysis using the OpenMEE application. The research results stated that, based on the analysis of 8 reputable international journals, the estimated Effect Size (ES) value was 0.357 in the medium category (0.2 ≤ ES ≤ 0.8) and the p-Value < 0.001. Meanwhile, heterogeneous analysis shows that the Tau^2 value is 0.127 with an I^2 of 89.434, meaning that the diversity of variance from the journal studies analyzed has a very significant effect. Meanwhile, the results of the effect size analysis based on the learning model stated that there were 3 learning methods that obtained an estimated Effect Size (ES) value in the high category, including: Green Learning Method (GeLem) obtained an estimated effect size value of 3.797, a learning method based on local wisdom obtained a value The estimated effect size was 1.665, and the Virtual Field Trip assisted by Augmented Reality obtained an estimated effect size value of 0.974. Furthermore, the results of the effect size analysis of biodiversity literacy abilities at various levels of education stated that high school students had higher biodiversity literacy abilities compared to other levels of education, namely 1.281 in the high category (ES ³ 0.8). This research also analyzes the effect size value based on biodiversity literacy indicators. Based on 10 biodiversity literacy indicators, only one indicator shows the highest estimated effect size value compared to other indicators, namely the environmental knowledge indicator of 1.813. Thus, it can be concluded that there is a significant influence in increasing biodiversity literacy skills based on learning methods and level of education.